Reconfiguring Language Curriculum Paradigms: A Critical Comparative Study of English and Arabic for Foreign Language Learners - Sarwadi Sarwadi; Lalu Agus Muzaki; Azwardi Pazli; Baiq Susi Apni Khaerawati; Baiq Nila Rahma Putri; Ahmad sulbi (IJECA (International Journal of Education and Curriculum Application), 2026)
The growing demand for communicative competence and digital adaptability in the era of globalization necessitates a critical re-examination of foreign language curriculum paradigms. Despite extensive research in language education, comparative and critical analyses of English and Arabic curricula remain limited and fragmented. This study aims to analyze and reconfigure language curriculum paradigms through a critical comparative examination of English and Arabic curricula for foreign language learners. This study employs a qualitative research design integrating comparative analysis and Critical Discourse Analysis (CDA) to explore pedagogical practices, curriculum structures, and underlying epistemological and ideological dimensions. Data were collected from 12 curriculum documents, 8 instructional textbooks, and selected scholarly publications from English and Arabic language programs in higher education institutions through purposive sampling and systematic document analysis. The analysis employed Norman Fairclough’s Critical Discourse Analysis (CDA) model, including textual analysis, discursive practice analysis, and social practice analysis to identify pedagogical orientations, ideological tendencies, and power relations embedded in the curricula. The findings reveal that English curricula are predominantly communicative, learner-centered, and technologically integrated, reflecting a global and adaptive paradigm. In contrast, Arabic curricula emphasize grammatical accuracy, textual comprehension, and knowledge preservation, indicating a structural and tradition-oriented paradigm. CDA further reveals that English curricula promote global communicative and technology-oriented discourses, whereas Arabic curricula emphasize linguistic authenticity, textual authority, and cultural preservation within language education.